2016
DOI: 10.1097/md.0000000000005566
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intraoperative dexmedetomidine with intravenous anesthesia on postoperative emergence agitation/delirium in pediatric patients undergoing tonsillectomy with or without adenoidectomy

Abstract: Postoperative emergence agitation/delirium (POED) is a common complication in pediatric surgery patients, which increases the risk of developing postoperative airway obstruction and respiratory depression. This study aims to investigate the safety and efficacy of intraoperative infusion of dexmedetomidine (DEX) and its effects on POED in pediatric patients undergoing tonsillectomy with or without adenoidectomy.Sixty patients scheduled for tonsillectomy with or without adenoidectomy, aged 2 to 8 years, were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 34 publications
4
39
1
2
Order By: Relevance
“…A prolongation of the extubation time was not observed in our study when dexmedetomidine was administered, in contrast to the current literature . In their meta‐analysis of 9 trials regarding the effect of dexmedetomidine on extubation time under sevoflurane anesthesia, Zhang et al found that dexmedetomidine prolonged the extubation time compared to placebo ( P < .001).…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…A prolongation of the extubation time was not observed in our study when dexmedetomidine was administered, in contrast to the current literature . In their meta‐analysis of 9 trials regarding the effect of dexmedetomidine on extubation time under sevoflurane anesthesia, Zhang et al found that dexmedetomidine prolonged the extubation time compared to placebo ( P < .001).…”
Section: Discussioncontrasting
confidence: 97%
“…Regarding blood pressure recordings, we presume that the dose of dexmedetomidine of 1 mcg kg −1 and the concomitant use of propofol instead of sevoflurane in our study may be responsible for the lack of significant difference in blood pressure drop between the 2 groups of our patients. Similar to our anesthetic plan, administration of dexmedetomidine 1 mcg kg −1 followed by 0.5 mcg kg −1 h −1 in children under TCI propofol and remifentanil anesthesia for adenotonsillectomy revealed a decrease in heart rate, but no difference in blood pressure compared to control in the study by Cao et al…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…15 Because the terminal half-life of remifentanil is 3.5 min in children aged 2-7 years 16 and average operation time was about 20 min in remifentanil group, analgesic and sedative property of remifentanil were not likely to influence on EA. 22 There are some limitations to this study. Recent reports put forward the hypothesis of different brain networks in recovery phenomenon from sevoflurane anaesthesia in contrast with propofol.…”
Section: Discussionmentioning
confidence: 94%
“…Fifteen studies with 1,552 participants were included for the meta-analysis, and the results of the study characteristics were described in Table I. Outcomes for analysis were postoperative pain (pain scores) in the postanesthesia care unit (PACU), [10][11][12][13][14][15][16][17][18] postoperative analgesic requirements (doses of postoperative opioids or nonopioid analgesics), 4,8,[10][11][12]16,17,[19][20][21][22][23][24][25][26][27][28][29][30] postoperative agitation (agitation scores and incidence during recovery), 8,10,11,13,[15][16][17][18][19][21][22][23]31 desaturation, 8,10,15,17,18,20,…”
Section: Data Extraction and Risk Of Bias Assessmentmentioning
confidence: 99%